2012
DOI: 10.1002/ajmg.a.34413
|View full text |Cite
|
Sign up to set email alerts
|

The importance of advanced parental age in the origin of neurofibromatosis type 1

Abstract: Von Recklinghausen neurofibromatosis (NF1) is an autosomal dominant disorder with a prevalence about 1/3,000 (1/2,000-1/5,000 in various population-based studies). About 30-50% of cases are sporadic, resulting from a new mutation. NF1 is fully penetrant by mid-childhood, stigmata, and medical problems (neurological, dermatological, endocrine, ophthalmological, oncological) are highly variable. Advanced paternal age (APA) has been known to increase the risk of new germline mutations that contribute to the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The risk for genetic defects increases linearly for some conditions, and exponentially for others [Toriello et al, 2008]. Previous studies have shown that NF1 exhibits a paternal age effect (PAE) in sporadic cases [Bunin et al, 1997;Toriello et al, 2008;Snajderova et al, 2012] while advanced paternal age was observed among cohorts of sporadic NS cases and that a significant sex-ratio bias favoring transmission to males was present in subjects with sporadic NS caused by PTPN11 mutations [Tartaglia et al, 2004].…”
Section: Resultsmentioning
confidence: 96%
“…The risk for genetic defects increases linearly for some conditions, and exponentially for others [Toriello et al, 2008]. Previous studies have shown that NF1 exhibits a paternal age effect (PAE) in sporadic cases [Bunin et al, 1997;Toriello et al, 2008;Snajderova et al, 2012] while advanced paternal age was observed among cohorts of sporadic NS cases and that a significant sex-ratio bias favoring transmission to males was present in subjects with sporadic NS caused by PTPN11 mutations [Tartaglia et al, 2004].…”
Section: Resultsmentioning
confidence: 96%
“…Sporadic NF1 cases without a family history comprise 30% -50% among all NF1 patients, and the significance of advanced paternal age has been indicated [8] [9]. Those cases are caused by a novel mutation in the NF1 gene in the germ cell of either parent.…”
Section: Discussionmentioning
confidence: 99%
“…The nasopharyngeal carcinoma[18] is very rare in childhood and differs from its adult counterpart in the prevalence of the non-keratinizing, undifferentiated subtype and by an advanced clinical stage at onset and better chances of survival; peripheral PNET of the chest wall[19] is a rare malignant tumor that shares a similar histology, immunohistology and cytogenetics to Ewing's sarcoma and usually occurring in children; renal PNET[20] are also exceptional and belong to the vast group of peripheral malignant primary neuroectodermal tumours; mixed malignant mesenchymal tumors[212223] are also rare sarcoma that have been reported that originating from the cerebellar vermis, uterine tube and breast; undifferentiated sarcomas[24] are primitive mesenchymal tumors that can not be classified among standardized histopathologic entities; primary bone rhabdomyosarcoma[25] is also rarely seen in childhood; although hepatoblastoma[26] is the most common primary hepatic malignancy in childhood, it is quite rare and accounting for only 0.9% of all pediatric cancers; choroid plexus carcinomas[27] are rare tumors with dismal prognosis; primary gastric carcinoma[28] accounts for only 0.05% of pediatric gastrointestinal malignancies and its, presentation are similar to those of adult gastric carcinoma, intrarenal pheochromocytoma[29] (paraganglioma) is a very rare tumour and its diagnosis is often difficult; sertoli cell tumors[30] are frequently benign rare tumors and are seen in children before 1 year of age; cystic lymphangioma[31] is an uncommon congenital neoplasm which frequently occurs in young adults and <1% are localized in the mediastinum; giant congenital nevi[32] are seen rarely and disfiguring, potentially malignant pigmented nevi present at birth; atypical fibroxanthoma[33] is a nodular dermal ulcerative lesion with a favorable prognosis and most commonly occurs on sun-exposed skin in elderly individuals, neurofibromatosis (NFI)[34] is an autosomal dominant disorder with a prevalence about 1/3000 (1/2000-1/5000 in various population-based studies) and about 15% children with NFI develop optic pathway glioma[35] so the neurofibromatosis society recommend annual ophthalmic screening; juvenile xanthogranuloma[36] is one of the most common forms of non-Langerhans cell histiocytosis in children, although it usually presents as a self-limited skin lesion with typical histopathology, it can be challenging to diagnose due to an atypical initial presentation; orbital lymphangioma[37] is an uncommon, benign cystic lesion and usually presents with a slowly progressive proptosis, displacement of the globe, ptosis and restriction of eye movements in childhood; schwannomas[38] are being the most frequently encountered neurogenic tumours type of the posterior mediastinum that can be either benign or malignant, although the former is more common; hereditary multiple exostoses[39] is an autosomal dominant condition characterized by growth of multiple benign cartilage-capped tumors and greatly increases the relative risk to develop chondrosarcoma although most chondrosarcomas are sporadic; adrenocortical carcinoma[40] is a rare tumor and its incidence is ...…”
Section: Discussionmentioning
confidence: 99%